Disseminated Ochroconis gallopava infection in a heart transplant patient. Issue 3 (21st April 2013) - Cardeau‐Desangles, I.; Fabre, A.; Cointault, O.; Guitard, J.; Esposito, L.; Iriart, X.; Berry, A.; Valentin, A.; Cassaing, S.; Kamar, N.
Abstract Ochroconis gallopava is an emerging cause of mycosis in solid organ transplant recipients. Herein, we report a rare case of disseminated O. gallopava infection that involved lung, subcutaneous area, brain and peritoneum in a heart transplant recipient. Despite voriconazole therapy, the patient died 2 months after diagnosis.